; Agricultural policy in wheat production and crop diversification in Uzbekistan - Igor Pugach; Yuliy Yusupov; Zafar Berdinazarov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
, . . , . , . , , . (, .), . – – During the period of independence following the collapse of the Soviet Union, official statistics show that wheat production in Uzbekistan increased eightfold, while the sown area almost tripled. This, however, had no positive impact on either the quality of the wheat or its profitability for the newly established farms. Currently the land tenure system overloads farmers with additional obligations and, thus, further reduces their economic incentives. The main question that needs to be asked, therefore, is how this increase in wheat production came about. Factors that could have led to this are the new organizational form of agricultural production, the change in farm size, the mechanism of state procurement of agricultural output as well as land tenure insecurity for farmers. In addition, one also needs to question the reliability of official statistics on wheat production and the accuracy of this expansion. Reforms in the system of obligatory state production targets in cotton and wheat could increase farmers' incentives for more efficient land use and expand their capacities for crop diversification towards high value crops such as fruits, vegetables and fodder. This would also have a direct effect on the export potential of the agricultural sector.
urn:nbn:de:gbv:3:2-69664
Keywords: P41; P47; Q15; Q18; 330; food policy; state procurement system; agricultural diversification; export potential; Uzbekistan